2020
DOI: 10.1111/cbdd.13655
|View full text |Cite
|
Sign up to set email alerts
|

Identify old drugs as selective bacterial β‐GUS inhibitors by structural‐based virtual screening and bio‐evaluations

Abstract: Irinotecan (CPT‐11) is a cytotoxic drug that has wide applicability and usage in cancer treatment. Despite its success, patients suffer dose‐dependent diarrhea, limiting the drug's efficacy. No effective therapy is available for this unmet medical need. The bacterial β‐glucuronidase (β‐GUS) plays pivotal role in CPT‐11‐induced diarrhea (CID) via activating the non‐toxic SN‐38G to toxic SN‐38 inside intestine. By using structural‐based virtual screening, three old drugs (N‐Desmethylclozapine, Aspartame, and Gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…26 For example, pyrazolo [4,3-c]quinoline derivatives (TCH-3562) and uronic isofagomine derivatives could reduce CPT-11-induced complications without impairing its efficacy. [27][28][29] Reducing CPT-11 toxicity could in turn increase patients' tolerance to higher dosage, leading to better therapeutic outcomes. 30 This example illustrates the reciprocal interactions between commensal bacteria and chemotherapy, demonstrating the potential of microbiota modulation in reducing therapeutic toxicity and enhancing efficacy.…”
Section: Gut Bacteria and Pharmacokinetics Of Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…26 For example, pyrazolo [4,3-c]quinoline derivatives (TCH-3562) and uronic isofagomine derivatives could reduce CPT-11-induced complications without impairing its efficacy. [27][28][29] Reducing CPT-11 toxicity could in turn increase patients' tolerance to higher dosage, leading to better therapeutic outcomes. 30 This example illustrates the reciprocal interactions between commensal bacteria and chemotherapy, demonstrating the potential of microbiota modulation in reducing therapeutic toxicity and enhancing efficacy.…”
Section: Gut Bacteria and Pharmacokinetics Of Chemotherapymentioning
confidence: 99%
“…Selective β-glucuronidase inhibitors have now been developed to prevent CPT-11-induced microbial alteration and epithelial damage 26. For example, pyrazolo[4,3-c]quinoline derivatives (TCH-3562) and uronic isofagomine derivatives could reduce CPT-11-induced complications without impairing its efficacy 27–29. Reducing CPT-11 toxicity could in turn increase patients’ tolerance to higher dosage, leading to better therapeutic outcomes 30.…”
Section: Microbiota and Chemotherapymentioning
confidence: 99%
“…Another study also showed that gmGUS with loop 1 structure could process SN38-G more effectively than other types, based on which, the loop 1-targeted GUS inhibitor UNC10201652 was synthesized and showed great activities in blocking irinotecaninduced intestinal damage (Bhatt et al, 2020). In this regard, structure-based high-throughput screening may be a useful strategy for gmGUS inhibitor development (Wallace et al, 2010;Dashnyam et al, 2018;Feng et al, 2018;Chen et al, 2020;Jariwala et al, 2020).…”
Section: Pharmacological Intervention By the Specific Enzyme Inhibitormentioning
confidence: 99%
“…They found that nialamide, isocarboxazid, phenelzine, amoxapine, and mefloquine had significant inhibitory activity in vitro , respectively ( Ahmad et al., 2012 ). Three older drugs (aspartame, N-desmethylclozapine and gemifloxacin) have also been shown to have β-glucuronidase inhibitory activity using enzyme-based assays ( Chen et al., 2020 ). In vivo studies have indicated that amoxapine alleviates CPT11 toxicity and enhances the anti-tumor efficacy (to a certain extent) in tumor-bearing mice, and that the pharmaceutical activity of CPT11 is associated with its inhibitory impact on β-glucuronidase from E. coli , Enterococcus spp., Streptococcus spp., Escherichia spp., and Staphylococcus spp.…”
Section: Microbiota As An Intermediary In the Efficacy And Toxicity Of Cpt11 Chemotherapymentioning
confidence: 99%